(untitled) (e-Journal of Linguistics, 2023)
This study aimed to analyze the procedures involved in translating English adverbials of manner into Indonesian. The data were taken from a bilingual biography entitled "Against All Odds." A qualitative methodology was employed in this study. Additionally, the data were analyzed using the translation procedure theory proposed by Vinay and Dalbernet in Venuti (2010). The results of the data analysis are presented using a narrative approach and descriptive sentences. According to the findings of this study’s analysis, the English adverbials of manner can be translated into Indonesian by applying two methods, namely direct and oblique. Direct methods can be divided into borrowing, calque, and literal procedures. Meanwhile, oblique methods consist of equivalence and transposition procedures.